Estimation of the economic impact of bovine fascioliasis in Chile from 2011 to 2020 - Olivares-Ferretti, Pamela (2025)
Fasciola hepatica is a parasite that affects livestock, causing a significant economic impact due to reduced meat and milk production. This study analysed the economic impact of fascioliasis on Chilean livestock during the period 2011-2020 is analysed. Data were collected from government reports, and economic losses associated with fascioliasis were estimated. The results show that total economic losses amounted to 306 871 million Chilean pesos (CLP), with a significant increase in recent years. Losses in milk production were more substantial than losses in meat production, which is attributed to the larger dairy cattle population in the country. The regions of Los Lagos and Los Ríos were the most affected, as they concentrate the highest milk production and also exhibit a high prevalence of fascioliasis. The study highlights the importance of controlling this disease in Chilean livestock and suggests implementing management strategies to mitigate economic losses.